The Secret Listeners - Sinclair Mckay (London, United Kingdom AURUM PRESS, 2013)
Behind the celebrated code-breaking at Bletchley Park lies another secret...The men and women of the 'Y' (for Wireless') Service were sent out across the world to run listening stations from Gibraltar to Cairo, intercepting the German military's encrypted messages for decoding back at the now-famous Bletchley Park mansion. Such wartime postings were life-changing adventures - travel out by flying boat or Indian railways, snakes in filing cabinets and heat so intense the perspiration ran into your shoes - but many of the secret listeners found lifelong romance in their far-flung corner of the world. Now, drawing on dozens of interviews with surviving veterans, Sinclair McKay tells their remarkable story at last.
Keywords: War -- War